Islamic Household Accounting Model in Ultra Micro Debt Management as Social Inclusion - Gustiningsih, Diah Ayu; Ramlah, St.; Sunarti, Sunarti (SENTRALISASI, 2025)
This study was conducted with the aim of building an Islamic household accounting model in debt management as a form of social inclusion in ultra-micro households (UMi). The implications of this model are expected to reduce the risk of payment default. This study uses a qualitative method, an ethnomethodological approach with the first stage being the search for indexicality, the second stage being reflexivity that underlies practical action and the third stage being the achievement of contextual action that can be analyzed. The results of the study found that a complex High Touch mentoring model is very much needed for UMi debt management in Islamic households, low understanding of literacy and financial management and high motivational needs cause not only the need for funds needed by this household, but also strengthening social capital that can be built through complex mentoring.